Learning To Trust: Towards a Values-Driven Approach in Development Management. A Case Study of an American Non-Profit Organization - Ho, Candida (My University, 2012)
The management process between headquarters and field offices in international non-profit organizations is a little studied area. In this relationship, the organization faces the multifold challenges of maintaining cohesive identity and goals, pursuing a social mission, and maintaining a positive and empowering work environment for the motivation of the field office staff. Trust has been identified as the key to maintaining a positive headquarter-field office relationship. A values-driven organization culture and values-based human resource practices that focus on the development of staff and close adherence to the social mission build trust. Staff training also builds the competencies of field office staff and creates goodwill and opportunities for relationship building. This research explores how organization culture, human resource practices and trainings work together to create a trusting headquarters-field office relationship for both strategic and ethical purposes that are benefitting to the mission and ethos of a humanitarian organization through a values-driven organization culture. It also aims to describe how exactly the relationship functions and is perceived by headquarters. It also seeks to explore how selected human resource approaches and trainings build trust between headquarters and field offices. This study has been approached with the qualitative method of a single case study on International Justice Mission, a Christian humanitarian organization, located in Washington DC. Thirteen semi-structured interviews were carried out with selected staff from the human resource and managers of field offices located at headquarters. More than a values-driven culture, the results show that a unique achievement- oriented culture followed by its spiritual mission account much for the success of the organization. However, greater awareness of building relationships as a two-way engagement with field offices instead of merely working through them to attain goals builds trust and strengthens the overall culture as well. Human resource management performs three main roles in building trust: fair personnel policies, communication, and goal alignment through various types of training, especially orientation and leadership trainings. Proper communications by human resources is especially important for a non-profit organization as a motivation tool. While training is important for values-alignment and thereby inculcates trust, there is more need for local leaders to train local staff for better alignment of values between organization and local cultural values that is befitting of the ethos of development management.
Keywords: headquarter-field office relationship; values-based management; trust; organization culture; human resource management; training programs; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|